Prevalence of major depressive disorder in adult patients with alcohol use disorder admitted in the psychiatric ward at the Jigme Dorji Wangchuck National Referral Hospital, Thimphu, Bhutan - Bikram Chhetri; Ugyen Dem; Zimba letho; Kipchu Tshering; Borut Skodlar (Population Medicine)
Introduction The increasing prevalence of major depressive disorder (MDD) in alcohol use disorder (AUD) is associated with detrimental consequences, affecting the course and outcome of each disorder. The objective of this crosssectional study was to study the prevalence and severity of MDD and associated risk factors in Bhutanese adult patients with AUD admitted to the psychiatric ward, YJigme Dorji Wangchuck National Referral Hospital, from March 2020 to February 2021.